Anti-Remodeling Cardiac Therapy in Patients With Duchenne Muscular Dystrophy, Meta-Analysis Study - Raccah, Bruria Hirsh; Biton, Bar; Amir, Offer; Gotsman, Israel; Nahman, Dean; Matok, Ilan (Frontiers in Pharmacology, 2022)
Background: Almost all Duchenne muscular dystrophy (DMD)patients that reach their 30s present cardiomyopathy. There is no sufficient proof of the efficacy of anti-remodeling cardiac therapy for DMD cardiomyopathy (DMDCM). As a result, this population remains under-treated. Our aim is to assess the efficacy of anti-remodeling cardiac therapy for DMDCM by using meta-analysis. Methods: PubMed (MEDLINE), Embase, and Cochrane library were searched through January 2021. Randomized control trials, case-control studies, and observational studies that reported assessments of cardiovascular outcomes and death of participants using angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, beta-blockers, mineralocorticoid-receptor antagonists and Ivabradine, were included. The primary outcome was total mortality. Secondary outcomes included changes in left ventricular ejection fraction (LVEF), serum natriuretic peptide levels (BNP), and heart rate (HR). Data were extracted for eligibility by two independent reviewers. Random-effects meta-analysis was used to pool results. Results: Twelve studies with 439 patients were included in our meta-analysis. Treated patients have lower HR, mean difference of -17 beats per minute (CI [-25]-[-9], p<0.01). The LVEF was improved in treated patients, with a mean difference of LVEF 3.77% (CI 0.44 – 7.12, p<0.03). Although mortality rates did not reach statistical significance there was a trend for total mortality reduction (hazard ratio 0.36, CI (0.1-1.25), p=0.107) and for BNP reduction (SSMD: 0.141, CI ([-0.19]-[0.47]), p=0.3). Conclusions: Pharmacologic treatment for DMDCM patients is associated with decreased HR and improved LVEF. Therefore, DMDCM patients may benefit from implementing guideline therapy for HF.